Peningkatan Endorsement NCT Dream sebagai Brand Ambassador melalui Brand Image dan Brand Awareness guna Mengoptimalkan Purchase Decision (Studi Kasus pada Konsumen Mie Instan Lemonilo di Kabupaten Semarang) - Panca Nur Hayati; Teguh Harso Widagdo; Satria Avianda Nurcahyo; Ahmad Ali (ARZUSIN, 2026)
The increasingly intense competition in the instant noodle industry requires companies to optimize marketing strategies capable of building brand image and brand awareness in the minds of consumers, one of which is the use of public figures as brand ambassadors. This study aims to analyze the effect of NCT Dream’s endorsement as a brand ambassador on consumers’ purchase decisions for Lemonilo Instant Noodles, with brand image and brand awareness as mediating variables. A quantitative approach with an explanatory research design was employed, with data collected through questionnaires from 100 consumers of Lemonilo Instant Noodles in Semarang Regency who had been exposed to NCT Dream’s endorsement, selected using purposive sampling. Data were analyzed using multiple linear regression and path analysis with the assistance of SPSS 25. The results show that the brand ambassador has a positive and significant effect on brand image, brand awareness, and purchase decisions, and that all independent variables simultaneously and partially have a significant effect on purchase decisions. Mediation tests further demonstrate that brand image and brand awareness significantly mediate the effect of the brand ambassador on purchase decisions. The study concludes that strengthening the role of NCT Dream as a brand ambassador is effective in shaping positive consumer perceptions and enhancing brand recall, which ultimately drives purchase decisions. The implications underscore the importance of celebrity endorsement strategies that are integrated with efforts to reinforce brand image and brand awareness in order to increase the marketing effectiveness of instant noodle products.